ANALISIS PERENCANAAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY DENGAN PERTIMBANGAN STOCKOUT COST (Studi Kasus Pada PT. Multi Logam Presisi) - Hendy Tannady; Yohanes Dwi Pratama (Universitas Ahmad Dahlan Indonesia, 2019)
The demand for erratic products makes the company must control raw material inventory. This study aims to minimize the total costs associated with supplying raw materials by determining the appropriate inventory control methods for the company. Research using the probabilistic inventory method because there are costs associated with shortages (stockout cost), if there is a shortage of inventory the company will do a back order (back order) to meet existing demand.The analysis shows that the calculation of probabilistic inventory models provides lower costs compared to the company method. The optimum number of orders with the EOQ method is 25,95 kg. The company experienced a stock out of 38,06%. The company resolved the problem by paying a fee of Rp 32.869,70. Inventory planning using the EOQ method can save Rp 42.213,67.